Challenges and solutions in diagnosis and treatment of obesity - FANG Ping, HAN Junfeng (Zhenduanxue lilun yu shijian, 2025)
According to the World Health Organization (WHO), 2.5 billion adults worldwide were overweight, accounting for 43%, and 890 million were obese, accounting for 16% in 2022. Notably, the onset of obesity has shifted towards younger age groups, with a fourfold increase in adolescent obesity cases worldwide since 1990. China has the highest prevalence and growth rate of overweight/obesity globally. According to the latest Report on Residents' Nutrition and Chronic Diseases (2020), China's rate of overweight and obesity in adults has reached 50.7%, a figure projected to reach 65.3% by 2030. Overweight and obesity can lead to metabolic, functional, and psychological disorders, serving as critical risk factors for mortality and disability. They have emerged as one of the greatest medical challenges facing humanity. Currently, overweight/obesity diagnosis relies primarily on body mass index (BMI), body composition analysis, and imaging techniques. Advances in biomarkers and genomics have facilitated the early identification and diagnosis of obesity. However, conventional anthropometric measurements in clinical practice fail to reflect fat distribution or predict disease prognosis. In recent years, experts both in China and abroad have proposed new advanced frameworks for obesity diagnosis and treatment, emphasizing that comprehensive assessment should integrate anthropometric measurements with clinical evaluation of weight-related complications and their severity. Due to regional and ethnic differences in obesity diagnosis, there is an urgent need to develop obesity diagnosis, staging, and management frameworks aligned with the characteristics of China's population, thereby improving the identification of obesity and its related diseases and standardizing patient management strategies. Pharmacotherapy for obesity is favored by many patients due to its good efficacy, compliance, and non-invasive nature. However, pharmacotherapy faces challenges including adverse effects, muscle loss during weight reduction, and weight rebound after discontinuation. Emerging strategies, such as developing small molecule oral drugs, combination therapies, and peptide-drug conjugates, may offer novel solutions to improve tolerability, optimize weight loss experience, and achieve long-term weight maintenance.